Anteseden Niat Kewirausahaan Berkelanjutan Gen Z Kawasan Smart City Semarang: Apakah Teknologi dan Pemerintah Daerah Berperan? - Muhammad Alfarizi (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2023)
The UN Agenda for Sustainable Development 2030 focuses on entrepreneurship as a solution to turn ideas into action in building smart cities. Research states that entrepreneurship is crucial in creating sustainable companies in growing cities. Smart City is becoming a center for innovation and data technology to improve city services. Semarang City, as the center of economy and education in Indonesia, has implemented the Smart City concept since 2013. The rapid development of this city, together with the demographic bonus of Generation Z, supports the implementation of technological solutions in support of an adaptive and sustainable Smart City concept. This study aims to investigate the influence of urban entrepreneurship and entrepreneurship education on the sustainable entrepreneurial intentions of Gen Z in the Smart City Area, in this case study Semarang City, by considering the moderator of the role of technology and local government support. This study proposes six hypotheses according to the proposed model of sustainable entrepreneurship in Smart City areas with moderation of business technology and government support. This study chose a survey-based quantitative approach on 250 local Semarang students, and the response data was analyzed using the SEM-PLS technique. The results showed that urban entrepreneurship and Entrepreneurship Education significantly positively affect the sustainable entrepreneurial intentions of the Smart City area.Furthermore, it is proven that business technology and local government support moderate relations between urban entrepreneurship and Entrepreneurship Education with the intention of sustainable entrepreneurship in the Semarang Smart City area. The study recommends the integration of the concept of entrepreneurship in the college curriculum and the establishment of partnerships between universities, industry, and government in Semarang City. The government must expand internet connectivity, provide training programs for entrepreneurs, utilize technology in city infrastructure, and collaborate with educational institutions and industry for inclusive and innovative economic growth.